PERANCANGAN MODEL BISNIS BANK SAMPAH DI KOTA BANDUNG MENGGUNAKAN BUSINESS MODEL CANVAS - Salsabila Aliya Nabilah; Dwi Purnomo; Roni Kastaman (Bina Ekonomi, 2019)
ABSTRACTA waste bank is a place for collecting and sorting dry waste. Waste is saved, weighed, and valued with a sum of money. Trash is sold in factories that worked with the waste bank. The waste bank engages people to sort waste and provide public awareness in managing waste and reducing waste that is transported to landfills. Waste segregation is one of the efforts made in the community to reduce the problem of household waste. Waste sorting is done so that the recycling process can be done more effectively and efficiently. Waste management with a waste bank system is expected to be able to assist the government in handling waste and improving the community's economy. The benefits of the waste bank are to help waste management, make the community aware of a healthy, neat, and clean environment, turning waste into something more useful. The method used to design a waste bank’s business model with a business model canvas. The results obtained by a complete framework regarding the resources, activities, and related parties needed to run a waste bank in Bandung.Keywords: waste bank; waste sorting; business model canvas